Managing the introduction of genomic applications into the National Health Service: A special challenge for health technology assessment in Italy - Pitini, Erica; Migliara, Giuseppe; Baccolini, Valentina; Isonne, Claudia; Mazzalai, Elena; Turatto, Federica; Salerno, Carla; Pagano, Federica; Menzano, Maria Teresa; De Vito, Corrado; Marzuillo, Carolina; Villari, Paolo (Frontiers in Public Health, 2022)
In recent years, the rapid proliferation of genomic tests for use in clinical practice has prompted healthcare systems to use a health technology assessment (HTA) approach to distinguish valuable from unwarranted applications. Here, we narratively review the Italian HTA mechanisms for medical devices (MDs), both at national and regional level, and discuss the opportunity and benefits of extending it to genomic technologies, for which a dedicated assessment path was advocated by the National Plan for Public Health Genomics in 2017. We found that the National Health Technology Assessment Program for MDs, completed in 2019, had developed a structured pathway for the HTA of MDs; it established a hub-and-spoke structure, run by a governmental institution, and put in place transparent methodological procedures to cover all four HTA phases (i.e., proposal and prioritization, assessment, appraisal, and dissemination). However, several factors have hindered its adoption, and the Regions are at different stages of its implementation. For these reasons, efforts should be made to ensure its effective deployment, both at national and regional level. In addition, we argue that, to harmonize the institutional roles and methodological procedures adopted, the time has come to concentrate resources on a single pathway for the assessment of all technologies that includes both MDs and genomic applications.